KAJIAN PATI JAGUNG DAN BUNGA ROSELA PADA KUALITAS PERMEN LUNAK (soft candy) - HP, Sudaryati; Latifah, Ir; Sari, Yapri Lukita (UPN VETERAN JAWA TIMUR, 2010)
Soft candy is mixtures of sucrose, glucose syrup, water, gel-forming materials and additives such as flavor, dye and has a soft texture. Roselle petals become alternative for the manufacture of soft candy roselle that have vitamin C and anthocyanins that serves as a natural red color. This soft chewy candy is produced from the gel-forming material. Corn starch as a gel-forming material, because the nature of corn starch in its contribution to the texture. Cooking is an important processing stage in the manufacture of candy that will affect the texture and color of the candies are produced. This study aims to determine the effect of adding corn starch and long ripening on the quality of roselle soft candy and to obtain the best combination treatment between the addition of corn starch and long cooking in the manufacture. This research method using a completely randomized design with 2 factors and repeated 3 times. The first factor was the concentration of corn starch (5%, 10%, 25%) and the second factor is the length of cooking (1.5 minutes, 3 minutes, 4.5 minutes). The Best research results soft candy corn starch concentration of 10% and long cooking 3 minutes to produce water content 5.712%, Vitamin C 27.78 mg/100gr, 56.060% total dissolved solids, texture 0.186 mm / gr.dtk and anthocyanin 0.0713%.Keywords: Software Candy, Rosela